How to read a dress : a guide to changing fashion from the 16th to the 21st century - Edwards, Lydia (Bloomsbury Visual Arts, 2021)
"With lavish color images and commentary on the key features of every major dress style across five centuries, How to Read a Dress is the ultimate guide to how fashions change and the ideal tool for identifying historical styles"- Resumé vydavatel
Terminologický slovník
Keywords: móda -- 16.-20. století; dámská móda -- 16.-20. století; dámské oděvy -- 16.-20. století; dějiny módy -- 16.-20. století; dějiny odívání -- 16.-20. století; odívání -- 16.-20. století; fashion -- 16th-20th centuries; women's fashion -- 16th-20th centuries; women's clothing -- 16th-20th centuries; history of fashion -- 16th-20th centuries; history of clothing -- 16th-20th centuries; clothing -- 16th-20th centuries; obrazové publikace; pictorial works; handbooks and manuals; příručky